Cubic Spinel XIn2S4 (X = Fe, Co, Mn): A New Type of Anode Material for Superfast and Ultrastable Na‐Ion Storage (Adv. Energy Mater. 44/2021). Issue 44 (23rd November 2021) - Yan, Dong; Li, Ke; Yan, Yaping; Huang, Shaozhuan; Von Lim, Yew; Shang, Yang; Fang, Daliang; Ang, Lay Kee; Yang, Hui Ying
Abstract : Na‐Ion Batteries In article number 2102137, Hui Ying Yang and co‐workers develop an isomorphous series of cubic spinel XIn2 S4 (X = Fe, Co, Mn) as a new type of Na‐ion battery anode, displaying superfast and ultrastable Na‐ion storage performance. The amazing results are due to the synergies between X substitution at the spinel's tetrahedral site and the inherent In skeleton at the octahedral sites.